Two-Dimensional Liquid Chromatography Method for the Determination of Gelsemium Alkaloids in Honey - Xiao Ma; Meng-Ting Zuo; Xue-Jia Qi; Zi-Yuan Wang; Zhao-Ying Liu (Foods, 2022)
Toxic Chinese medicine residues in honey pose a serious threat to consumer health. Gelsemium is one of the nine ancient poisons, making the whole plant virulent. The residue of Gelsemium alkaloid in honey causes poisoning from time to time. Therefore, it is very important to establish a method for the detection of Gelsemium alkaloids in honey. In this study, a method of solid phase extraction (SPE) with two-dimensional liquid chromatography (2D-LC) was developed for the first time for the simultaneous determination of Gelsemium alkaloids in honey, including gelsemine, koumine and humantenmine. First, the honey samples were purified by a PRS cation exchange column and extracted with 5% ammoniated methanol. Then, we verified the methodological indicators, which were in line with the Codex Guideline requirements. The verification results are as follows: matrix-matched calibrations indicated that the correlation coefficients were higher than 0.998. The recovery was in the range of 81%–94.2% with an intraday precision (RSD) of ≤5.0% and interday RSD of ≤3.8%. The limit of detection for the three alkaloids was 2 ng/g. The limits of quantification for gelsemine and koumine were 5 ng/g, and humantenmine was 20 ng/g. This method can be applied to the monitoring of Gelsemium alkaloids in honey.